Matrimony, Marriage and Migration in Mithila Region, India: An Exploratory Geographical Study of Saurath Sabh - Singh, Ravi S.; Sugandh (National Geographical Journal of India, 2022)
Marriage migration is important migration type in the patriarchal societies. The system of matrimony is considered crucial in the institution of marriage and associated negotiations. They together form significant social and cultural academic research issue particularly in India. This paper is a brief attempt to look into Saurath Sabha, which lies in linguistic region known as Mithila, popularly known for organizing matrimony fairs actively participated by Maithila Brahmins and Karna Kayasthas. Though this tradition is continuing since more than 700 years, due to contemporary impacts, decline in participation in the Sabha and loss of its charm is noticed in recent time. The analysis and discussion attempted are based mainly on literary sources.